Paclobutrazol and maleic hydrazide-induced growth inhibition in warm season turfgrasses through structural and physiological differences - Muhammad Mubashir Shahzad; Gulzar Akhtar; Muhammad Asif Shehzad; Sami Ullah; Hafiz Nazar Faried; Kashif Razzaq; Fahim Nawaz; Ishtiaq A. Rajwana; Muhammad Amin; Muhammad Ahsan (Kuwait Journal of Science)
Warm season turfgrasses are fast growing and require frequent mowing, which increases maintenance cost. Various plant growth retardants are used to reduce the growth and required amount of mowing of turfgrasses. Therefore, the present study was planned to explore the impact of paclobutrazol (PBZ) and maleic hydrazide (MH) on the growth rate and quality of warm season turfgrasses. Four turfgrasses were grown in pots at research area, MNS-University of Agriculture, Multan. Paclobutrazol (PBZ) and Maleic Hydrazide at 0.01%, 0.02%, 0.04% levels were applied through foliar application with three repeats in CRD arrangement. The data of growth, quality and anatomical attributes were evaluated. The results showed significant differences in growth and the quality of turfgrasses in response to different levels of plant growth retardants. PBZ application at 0.04% maximum reduced fresh (26%, 35%, 25%) and dry (45%, 54%, 34%) weights of shoot, root and clippings respectively in Fine Dacca turfgrass. Additionally, PBZ application decreased the amount of mowing (40%) compared to control. Fine Dacca also produced the highest visual quality turf with maximum Chlorophyll a (46.87%) and Chlorophyll b (60%) in comparison to nontreated turfgrasses. The minimum number and density of stomatal and mesophyll cells by 45%, 47% were also recorded in Fine Dacca at PBZ (0.04%) with respect to control. It is concluded that PBZ at 0.04% could be used to reduce the amount of mowing in warm season turfgrasses, which will decrease the cost of lawn maintenance and support the landscape industry.